Limited phenological and pollinator-mediated isolation among selfing and outcrossing Arabidopsis lyrata populations. Issue 1939 (25th November 2020) - Gorman, Courtney E.; Bond, Lindsay; van Kleunen, Mark; Dorken, Marcel E.; Stift, Marc
Abstract : Transitions from outcrossing to selfing have been a frequent evolutionary shift in plants and clearly play a role in species divergence. However, many questions remain about the initial mechanistic basis of reproductive isolation during the evolution of selfing. For instance, how important are pre-zygotic pre-pollination mechanisms (e.g. changes in phenology and pollinator visitation) in maintaining reproductive isolation between newly arisen selfing populations and their outcrossing ancestors? To test whether changes in phenology and pollinator visitation isolate selfing populations of Arabidopsis lyrata from outcrossing populations, we conducted a common garden experiment with plants from selfing and outcrossing populations as well as their between-population hybrids. Specifically, we asked whether there was isolation between outcrossing and selfing plants and their between-population hybrids through differences in (1) the timing or intensity of flowering; and/or (2) pollinator visitation. We found that phenology largely overlapped between plants from outcrossing and selfing populations. There were also no differences in pollinator preference related to mating system. Additionally, pollinators preferred to visit flowers on the same plant rather than exploring nearby plants, creating a large opportunity for self-fertilization. Overall, this suggests that pre-zygotic pre-pollination mechanisms do not strongly reproductively isolate plants from selfing and outcrossing populations of Arabidopsis lyrata .